Participatory rural governance in India - Datta, Prabhat; Bhattacharyya Sen, Panchali (2000)
Probing participatory rural governance in India through the institution of Gram Sabhas, the basic unit, the authors first examine its structure, nature, and evolution. Imparting focus on West Bengal's Gram Sansad, they make a comparative assessment on its efficacy vis-a-vis Gram Sabhas in other states. Concentrating on enhancing people's participation, they give some weightage to West Bengal experience and conclude by prescribing certain measures which need to be implemented to obtain the desired advantage of people's participation. - Reproduced
Keywords: Panchayat - India - West Bengal; Panchayat